2017
DOI: 10.1159/000480210
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Peroxide Induces Lipid Raft-Mediated STAT-6 Activation in T Cells

Abstract: Background/Aims: CD4+ T cells are a critical component of the adaptive immune response. While the mechanisms controlling the differentiation of the Th1, Th17, and regulatory T cell subsets from naïve CD4+ T cells are well described, the factors that induce Th2 differentiation are still largely unknown. Methods: The effects of treatment with exogenous H2O2 on STAT-6 phosphorylation and activation in T cells were examined by immunoblotting, immunofluorescence and gel shift assay. Anti-CD3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Oxidative stress is important for macrophage polarization, especially for M2 differentiation that is blocked by an inhibition of superoxide production [22]. Interestingly, STAT6 was shown to be involved in M2 macrophage polarization [23], and can be activated by ROS in T cells [24]. Thus it can be hypothesized that ROS may be responsible for the M2 polarization via STAT6 induction in SSc.…”
Section: Ros and Inflammation In Sscmentioning
confidence: 99%
“…Oxidative stress is important for macrophage polarization, especially for M2 differentiation that is blocked by an inhibition of superoxide production [22]. Interestingly, STAT6 was shown to be involved in M2 macrophage polarization [23], and can be activated by ROS in T cells [24]. Thus it can be hypothesized that ROS may be responsible for the M2 polarization via STAT6 induction in SSc.…”
Section: Ros and Inflammation In Sscmentioning
confidence: 99%
“…[ 9 , 13 , 16 ] Due to its permeability, H 2 O 2 serves as a secondary messenger molecule. [ 16 , 17 , 99 , 100 ] For instance, exposed thiol moieties (‐SH) on proteins can be oxidized by H 2 O 2 , altering protein conformation to favor either increases or decreases in enzymatic activities. [ 18 , 19 ] Concurrently, mitoROS contribute to the formation of other increasingly destructive ROS.…”
Section: Introductionmentioning
confidence: 99%
“…During the activation, T cells have increased clathrin-mediated endocytosis to fine-tune the TCR signaling strength and engage in macropinocytosis to access of extracellular amino acid for cell growth . The special cellular uptake inhibitors (PitStop, inhibitor of clathrin-mediated endocytosis; EIPA, inhibitor of macropinocytosis; MβCD, inhibitor of clathrin-independent endocytosis , ) were used to further explore the mechanism of PEAL NPs cellular uptake pathway. The uptake of PEAL NPs by rested and activated T cells was significantly blocked by PitStop compared to other inhibitors, which showed that the uptake of PEAL NPs was mainly mediated by clathrin-mediated endocytosis (Supporting Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitor was added into medium 15 min prior to addition of PEAL NPs. Final concentrations of inhibitors are as follows: 25 μM PitStop 2, 50 μM EIPA, or 2.5 mM MβCD (Sigma-Aldrich). , Then the rested or the activated T cells were co-cultured with PEAL cy5‑miNC NPs for 6 h before the cells were collected for measurement.…”
Section: Materials and Methodsmentioning
confidence: 99%